2012
DOI: 10.1097/iae.0b013e3182278b98
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Visual Acuity and Foveal Photoreceptor Integrity in Eyes With Chronic Cystoid Macular Edema Associated With Retinal Vein Occlusion

Abstract: Even if a large cystoid space is located in the fovea, its effect on deterioration of the underlying foveal photoreceptor cells is not as strong as is generally thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…It is likely that long-standing macular striae and edema leads to foveal photoreceptor dysfunction in a similar fashion as described for chronic cystoid macular edema, which ultimately limits the potential for visual recovery. 48 A third study of 177 eyes that underwent bleb revision for 1 of 3 different indications (hypotony without leak, bleb leak, and bleb dysesthesia), by Radhakrishnan and associates, showed that revision surgery provided successful resolution of bleb-related complications, with most patients maintaining good IOP control thereafter. 49 However, the relationship between duration of hypotony and final visual outcome was not evaluated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that long-standing macular striae and edema leads to foveal photoreceptor dysfunction in a similar fashion as described for chronic cystoid macular edema, which ultimately limits the potential for visual recovery. 48 A third study of 177 eyes that underwent bleb revision for 1 of 3 different indications (hypotony without leak, bleb leak, and bleb dysesthesia), by Radhakrishnan and associates, showed that revision surgery provided successful resolution of bleb-related complications, with most patients maintaining good IOP control thereafter. 49 However, the relationship between duration of hypotony and final visual outcome was not evaluated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…While in cystoid macular oedema, cysts seem not to have such a damaging effect on the photoreceptor layer, cystoid spaces in diabetic macular oedema have been suggested to be accompanied by photoreceptor damage and impaired IS ⁄ OS integrity (Kurashige et al 2012;Murakami et al 2012). Large cysts in the ONL of the retina in DME are suggested to occur in a rather late stage of DME and have a more severe negative impact on macular function by creating disorganization of photosensitive retinal tissue than smaller cysts or cystoid formation occurring in inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, the existence of ME showed no significant association with VA after anti-VEGF treatment. Kurashige et al [16] also suggested that total foveal retinal thickness had no significant association with VA, whereas the thickness of the foveal outer retina had a significant association with VA. On the other hand, strong associations between EZ disruption and VA have been reported [16-19]. Treatment for ME due to BRVO should aim to maintain the integrity of the outer retinal layer rather than to diminish ME itself.…”
Section: Discussionmentioning
confidence: 99%